PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS VIDEO ANIMASI PADA PEMBELAJARAN IPAS KELAS V SD - Arifah, Ummu; Lian, Bukman; Riyanti, Henni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the validity, practicality and effectiveness of the Development of Animation Video-Based Learning Media in Science Learning for Grade V Elementary School. The development of this research uses the ADDIE development model. The data collection techniques used by researchers are observation, documentation, questionnaires and tests. The results of the study showed that the validity test obtained an average of 91.65% which is included in the very valid category. Furthermore, the practicality test obtained an average of 91.00% in the one-to-one student response questionnaire and 93.67% in the small group student response questionnaire which is included in the very practical category. Then the results of the effectiveness test obtained an average of 94.55% which is included in the very effective category. These results indicate that animation video-based learning media in science learning for grade V elementary school is feasible to use.